Strengthening Religious Tolerance: The Practice of Harmony and Diversity of the Society of Ngargoyoso Village, Karanganyar, Central Java - Rohmatul Faizah; Jihan Avie Yusrina (Future Science, 2022)
This research is encouraged by the rise of news about conflicts in the name of religion in Indonesia and as a response to the low tolerance attitude of Indonesian towards other religions' activities. Therefore, it is necessary to show the best practice of inter-religious harmony as a reference in fostering a harmonious inter-religious life and dismissing conflict issues that are reported louder than its tolerance. This best practice can be found in Ngargoyoso Village, Karanganyar, Central Java, a village with multi-religion: Islam, Hinduism, and Christianity, that can live in harmony. The ministry even elects Ngargoyoso as a tolerance-aware village. For this reason, this study will photograph the tolerance conditions in Ngargoyoso and reveal the implementation of tolerance and diversity in the surrounding society. These two questions will be answered by qualitative research with a case study approach. The results indicate that harmony in Ngargoyoso has existed since ancient times until now. People used to see the practice of tolerance from an early age. The harmonious attitude is based on full awareness by society so that the existing tolerance is active. The spirit of cooperation also melts into the society's soul so that they have a sense of love for each other without considering religious differences. The implementation of tolerance and diversity in this village is based on Pancasila values ??so that harmony and togetherness are created. The limitation of tolerances is only on social affairs and not on worship matters. Various efforts to maintain a well-established tolerance continue to be carried out, including assistance from outside parties and a tolerance festival.